2012
DOI: 10.1007/s11259-012-9519-9
|View full text |Cite
|
Sign up to set email alerts
|

A transgenic Marc-145 cell line of piggyBac transposon-derived targeting shRNA interference against porcine reproductive and respiratory syndrome virus

Abstract: Porcine reproductive and respiratory syndrome (PRRS) is now considered to be one of the most important diseases in countries with intensive swine industries. The two major membrane-associated proteins of porcine reproductive and respiratory syndrome virus (PRRSV), GP5 and M (encoded by ORF5 and ORF6 genes, respectively), are associated as disulfide-linked heterodimers (GP5/M) in the virus particle. In this study, we designed 5 of the small hairpin RNAs (shRNAs) targeting the GP5 and M gene of PRRSV respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A recent report has declared that siRNA transgenesis could confer viral infection resistance to pseudorabies virus (PRV) on mice (Daniel-Carlier et al, 2013). Although it has been shown that transient delivery of siRNA by targeting viral genes protects susceptible cell lines (He et al, 2007), stable transgenic cell line presented stable inhibition to virus (Zhou et al, 2012), and recombinant adenovirusmediated RNAi guards animals against viral challenges , it remains unclear whether transgenesis of siRNA in pigs can confer permanent resistance against PRRSV infection. Previously, we designed siRNAs to target the open reading frame (ORF) 1b and 6 regions of PRRSV and showed that siRNA-1B372 targeting ORF1b had the strongest virus-inhibiting effect in MARC-145 cells.…”
Section: Introductionmentioning
confidence: 99%
“…A recent report has declared that siRNA transgenesis could confer viral infection resistance to pseudorabies virus (PRV) on mice (Daniel-Carlier et al, 2013). Although it has been shown that transient delivery of siRNA by targeting viral genes protects susceptible cell lines (He et al, 2007), stable transgenic cell line presented stable inhibition to virus (Zhou et al, 2012), and recombinant adenovirusmediated RNAi guards animals against viral challenges , it remains unclear whether transgenesis of siRNA in pigs can confer permanent resistance against PRRSV infection. Previously, we designed siRNAs to target the open reading frame (ORF) 1b and 6 regions of PRRSV and showed that siRNA-1B372 targeting ORF1b had the strongest virus-inhibiting effect in MARC-145 cells.…”
Section: Introductionmentioning
confidence: 99%
“…selectively inactivates the mRNA of the target gene. RNAi has been successfully used in infection inhibition studies of animal viruses, such as porcine epidemic diarrhea virus (PEDV) [15], influenza virus A [16], porcine transmissible gastroenteritis virus (TGEV) [17], and porcine reproductive and respiratory syndrome virus [18]. However, whether RNAi inhibits the replication of PDCoV has not been reported.…”
mentioning
confidence: 99%